CLINICAL STUDIES OF THE VACCINE PREPARATION FOR PREVENTION OF FLEXNER DYSENTERY ON THE BASIS OF MODIFIED SHIGELLA FLEXNERI LIPOPOLYSACCHARIDE (BASED ON THE RESULTS OF THE I PHASE OF CLINICAL TRIALS) - V. A. Lyodov (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The article presents the results of the I phase of clinical trials of a vaccine preparationfor prevention of Flexner dysentery on the basis of modified Shigella flexneri lipopolysaccharide on the limited contingent of adult volunteers (26 persons). Studying general and local post-inoculative reactions showed good acceptability and low reactogenicity of candidate vaccine "FLEXVAC®" in the doses from 25 to 100 gg. In the majority ofvolunteers immunized by the candidate vaccine "FLEXVAC®" we registered 4 and more times seroconversion of IgG and IgA classes antibodies playing basic role in the formation of adaptive anti-shigella immune response.